Characteristics of anemia in patients with Hashimoto's thyroiditis - Jandrić-Kočič Marijana (Association of Nurses Technicians and Midwives, 2019)
INTRODUCTION: Anemias is a frequent and often unrecognizable comorbidity of Hashimoto's thyroiditis. Hashimoto's thyroiditis suppresses erythropoiesis by reducing the proliferation of erythrocyte precursors, reducing erythropoietin production, lack of nutrients, including iron, vitamin B12 or folic acid, and comorbidities. OBJECTIVE: The aim of the study was to determine the characteristics of anemias in Hashimoto's thyroiditis. METHODS: The study was a cross section study conducted over a period of twenty-four months, from 01.11.2016. to 01.11. 2018. A total of 56 patients with newly diagnosed Hashimoto's thyroiditis and present anaemia's, 52 (93%) women and 4 (7.0%) men with an average age of 54 ± 5.1 years were evaluated. The data were collected on the basis of anamnesis, physical examination, available medical documentation, laboratory analysis and ultrasound examination. Data processing is done using standard statistical methods. RESULTS: Normocytic anaemia's are the most common type of anemias in Hashimoto's thyroiditis (67.9%). Microcytic anemias causing iron deficiency are the second most common (26.7%), while the presence of macrocytic anemias is rare (5.4%). CONCLUSION: Only an adequate etiological assessment of anemias in Hashimoto's thyroiditis guarantees successful causative therapy of the same.